RETRACTED: Mechanisms Contributing to the Generation of Mayer Waves - Ghali, Michael G. Z.; Ghali, George Z. (Frontiers in Neuroscience, 2020)
Mayer waves may synchronize overlapping propriobulbar interneuronal microcircuits constituting the respiratory rhythm and pattern generator, sympathetic oscillators, and cardiac vagal preganglionic neurons. Initially described by Sir Sigmund Mayer in the year 1876 in the arterial pressure waveform of anesthetized rabbits, authors have since extensively observed these oscillations in recordings of hemodynamic variables, including arterial pressure waveform, peripheral resistance, and blood flow. Authors would later reveal the presence of these oscillations in sympathetic neural efferent discharge and brainstem and spinal zones corresponding with sympathetic oscillators. Mayer wave central tendency proves highly consistent within, though the specific frequency band varies extensively across, species. Striking resemblance of the Mayer wave central tendency to the species-specific baroreflex resonant frequency has led the majority of investigators to comfortably presume, and generate computational models premised upon, a baroreflex origin of these oscillations. Empirical interrogation of this conjecture has generated variable results and derivative interpretations. Sinoaortic denervation and effector sympathectomy variably reduces or abolishes spectral power contained within the Mayer wave frequency band. Refractorines of Mayer wave generation to barodeafferentation lends credence to the hypothesis these waves are chiefly generated by brainstem propriobulbar and spinal cord propriospinal interneuronal microcircuit oscillators and likely modulated by the baroreflex. The presence of these waves in unitary discharge of medullary lateral tegmental field and rostral ventrolateral medullary neurons (contemporaneously exhibiting fast sympathetic rhythms [2–6 and 10 Hz bands]) in spectral variability in vagotomized pentobarbital-anesthetized and unanesthetized midcollicular (i.e., intercollicular) decerebrate cats supports genesis of Mayer waves by supraspinal sympathetic microcircuit oscillators. Persistence of these waves following high cervical transection in vagotomized unanesthetized midcollicular decerebrate cats would seem to suggest spinal sympathetic microcircuit oscillators generate these waves. The widespread presence of Mayer waves in brainstem sympathetic-related and non-sympathetic-related cells would seem to betray a general tendency of neurons to oscillate at this frequency. We have thus presented an extensive and, hopefully cohesive, discourse evaluating, and evolving the interpretive consideration of, evidence seeking to illumine our understanding of origins of, and insight into mechanisms contributing to, the genesis of Mayer waves. We have predicated our arguments and conjectures in the substance and matter of empirical data, though we have occasionally waxed philosophical beyond these traditional confines in suggesting interpretations exceeding these limits. We believe our synthesis and interpretation of the relevant literature will fruitfully inspire future studies from the perspective of a more intimate appreciation and conceptualization of network mechanisms generating oscillatory variability in neuronal and neural outputs. Our evaluation of Mayer waves informs a novel set of disciplines we term quantum neurophysics extendable to describing subatomic reality. Beyond informing our appreciation of mechanisms generating sympathetic oscillations, Mayer waves may constitute an intrinsic property of neurons extant throughout the cerebrum, brainstem, and spinal cord or reflect an emergent property of interactions between arteriogenic and neuronal oscillations.